PENGARUH TAKARAN PUPUK ORGANIK KOTORAN AYAM DAN PUPUK NPK TERHADAP PERTUMBUHAN TANAMAN JAGUNG HIBRIDA (Zea mays L.) - Asmawati, Asmawati; Palmasari, Berliana; Handoko, Lilik Dwi (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2021)
This study aims to determine and obtain the best dose of organic fertilizer for chicken manure and NPK fertilizer for the growth of hybrid corn (Zea mays L.) plants. This research has been carried out in Purwosari Village, Tanjung Lago Subdistrict, Banyuasin Regency. This research activity took place from May to August 2018. This study used factorial randomized block design (RBD) with 12 combinations, 3 replications, and 5 sample plants. The treatment is as follows: Organic Fertilizer Chicken Manure (O), O0 = 0 ton / ha, O1 = 5 tons / ha, O2 = 10 tons / ha, O3 = 15 tons / ha, NPK Fertilizer (A), A1 = 200 kg / ha, A2 = 300 kg / ha, A3 = 400 kg / ha. The variables observed in this study were plant height (cm), number of leaves (strands), leaf width (cm), root length (cm), plant dry weight (g). Based on the results of the analysis showed that the dose of organic fertilizer chicken manure had no significant effect on all the variables observed, the dose of NPK fertilizer had a very real effect on the leaf area variable, but had no significant effect on other variables. The conclusions that can be drawn from this study, the dose of organic manure of chicken manure 10 tons / ha and the dose of NPK fertilizer 300 kg / ha is the highest treatment for the growth of hybrid corn plants (Zea mays L.).